New Dimensions of Agricultural Extension: Forging Partnership - Dr. M.N. Reddy,; Dr. Vikram Singh, (Journal of Agricultural Extension Management, 2025)
Indian Agriculture has made rapid strides in the last half century by augmenting the annual food grain production from 51 million tones in the early fifties to 212 million tones in 2001-2002 and steered the country to a status of self-sufficiency. It has been successful in keeping pace with the rising food demand of a growing population. Food grain production quadrupled in the last 50 years while population nearly tripled from 350 million to one billion during this period. Significantly, the extension system had played its role untiringly in transfer of production technologies from lab to land besides the agricultural scientists, farmers and marketing network. Though the production has increased dramatically, not so much bothered about remunerative prices. Small and marginal farmers are generally prone to sell their produce on "as is where basis" due to several constrains